The Production of Carbon Nanofiber on Rubber Fruit Shell-Derived Activated Carbon by Chemical Activation and Hydrothermal Process with Low Temperature - Suhdi Suhdi; Sheng-Chang Wang (Nanomaterials, 2021)
Recently, the conversion of biomass into carbon nanofibers has been extensively studied. In this study, carbon nanofibers (CNFs) were prepared from rubber fruit shell (RFS) by chemical activation with H3PO4, followed by a simple hydrothermal process at low temperature and without a vacuum and gas catalyst. XRD and Raman studies show that the structure formed is an amorphous graphite formation. From the thermal analysis, it is shown that CNFs have a high thermal stability. Furthermore, an SEM/TEM analysis showed that CNFs’ morphology varied in size and thickness. The obtained results reveal that by converting RFS into an amorphous carbon through chemical activation and hydrothermal processes, RFS is considered a potential biomass source material to produce carbon nanofibers.